2019
DOI: 10.1007/s00167-019-05796-6
|View full text |Cite
|
Sign up to set email alerts
|

Adductor canal block is similar to femoral nerve block for the quality of rehabilitation after arthroscopic partial meniscectomy

Abstract: Purpose Adductor canal block (ACB) provides postoperative pain relief as effectively as femoral nerve block (FNB) does, and it preserves the strength of the quadriceps femoris. However, its effect on rehabilitation after arthroscopic partial meniscectomy has not been reported. The purpose of this study was to determine the effect of pre-operative ACB and FNB on the quality of rehabilitation after arthroscopic partial meniscectomy. Methods A total of 150 patients undergoing arthroscopic partial meniscectomy wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 28 publications
(28 reference statements)
0
19
0
Order By: Relevance
“…However, compared with the control or FNB group in ACL reconstruction, no superior analgesic benefits were found. 122 Another RCT of partial meniscectomy 157 and a systematic review of elective arthroscopic knee surgery 147 have produced similarly conflicting evidence in which a majority of outcomes demonstrated no significant analgesic benefits compared with a placebo or FNB 147 and an FNB alone. 157 Compared with the FNB's combined motor and sensory blockade, the ACB used for arthroscopic knee surgery appears to effectively decrease pain while also largely sparing quadriceps motor function.…”
Section: Knee Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…However, compared with the control or FNB group in ACL reconstruction, no superior analgesic benefits were found. 122 Another RCT of partial meniscectomy 157 and a systematic review of elective arthroscopic knee surgery 147 have produced similarly conflicting evidence in which a majority of outcomes demonstrated no significant analgesic benefits compared with a placebo or FNB 147 and an FNB alone. 157 Compared with the FNB's combined motor and sensory blockade, the ACB used for arthroscopic knee surgery appears to effectively decrease pain while also largely sparing quadriceps motor function.…”
Section: Knee Efficacymentioning
confidence: 99%
“…122 Another RCT of partial meniscectomy 157 and a systematic review of elective arthroscopic knee surgery 147 have produced similarly conflicting evidence in which a majority of outcomes demonstrated no significant analgesic benefits compared with a placebo or FNB 147 and an FNB alone. 157 Compared with the FNB's combined motor and sensory blockade, the ACB used for arthroscopic knee surgery appears to effectively decrease pain while also largely sparing quadriceps motor function. 1,2,47,98 In 2 ACL reconstruction trials, motor blockade was significantly greater with the FNB than the ACB at 1 hour 2 and at 0, 6, and 12 hours 47 after postoperative block administration, respectively, although other studies have found no differences in motor blockade throughout the 24 hours after administration.…”
Section: Knee Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…We felt this was justified because numerous studies have established that the adductor canal block provides equivalent analgesia to the femoral nerve block for multiple different procedures involving the lower extremity. [26][27][28] There is likewise no evidence that the anterior and posterior proximal sciatic nerve blocks produce any significant differences in analgesia in adults undergoing knee surgery. 29,30 We did not find any significant differences in pain scores, opioid usage, PASS scores or any measured outcome in either the femoral or adductor CPNB groups or the anterior or posterior sciatic groups in the subgroup analysis.…”
Section: Dovepressmentioning
confidence: 99%
“…Pain, especially early postoperative pain, can seriously affect postoperative limb function rehabilitation and can easily lead to physical stress reactions and a continuous release of inflammatory factors 10 . Analgesia management after knee surgery has been reported in knee arthroplasty, knee arthroscopy, and knee ligament reconstruction 11–13 . The commonly used analgesic schemes include general analgesia (GA), peripheral nerve block, and local or joint cavity injection analgesia 11–14 .…”
Section: Introductionmentioning
confidence: 99%